Cardiovascular evaluation in children with acute moderate to severe malnutrition - Ahmed Behairy; Fatma AlZahraa Mostafa; Rodina Sobhy; Bavly Ghattas; Noha Ali; Christine G. Salama (Egyptian Pediatric Association Gazette)
Abstract Introduction Child malnutrition is a worldwide health issue. The cardiovascular system, like all other systems, undergoes anatomical and functional alterations as a result of malnutrition. Objective To evaluate cardiovascular changes in patients with acute moderate to severe malnutrition. Methods This study was conducted on 82 participants. Forty-one cases of moderate and severe acute malnutrition diagnosed according to World Health Organization criteria and 41 participants were healthy controls. They were all subjected to full history taking, clinical evaluation, laboratory assessment, and cardiac condition assessment. Cardiac conduction was assessed using a 12-lead electrocardiogram (ECG). Cardiac dimensions and function were evaluated by tissue Doppler imaging (TDI), conventional echocardiography, and strain imaging echo (speckled tracking echocardiography). Results The participant’s ages ranged from 6 months to 5 years. The cases showed normal sinus rhythm with various ECG changes including prolonged PR interval, low-voltage ECG, especially in edema patients, inverted or flat T waves, and pathological waves, U-waves, associated with various electrolyte disorders as well as prolongation of corrected QT dispersion (QTcd). By conventional echo, no myocardial systolic function could be detected. A significantly lower global longitudinal strain (GLS) by strain imaging was found in the cases in addition to reduced muscle mass. TDI showed diastolic dysfunction in cases with acute malnutrition. No significant difference could be noted between both moderate and severe malnutrition apart from lower-voltage ECG and reduced 3D right ventricular ejection fraction in severe acute malnutrition cases. Conclusion Cardiac changes are noted in children with acute moderate or severe malnutrition using 12-lead ECG and echocardiography, most significantly subtle systolic dysfunction, diastolic dysfunction, low voltage ECG, and prolonged QTc dispersion. These changes are consistent with the presence of edema and electrolyte disturbances.